Lights out [videorecording (DVD)] - Jo Koy (Comedy Central ; Paramount, 2012)
Jo Koy's star continues to rise in his second, uncensored, stand-up special that was filmed at the Alex Theatre in Glendale California. Infectiously funny and painfully honest, Koy hits on such topics as the joys and struggles of fatherhood, growing up with strong and opinionated Filipino women, sleep apnea, and role playing. Special features: two featurettes.